Dividend Taxes and Firm Valuation: New Evidence - Auerbach, Alan J; Hassett, Kevin A (American Economic Review, 2006)
Dividend Taxes and Firm Valuation: New Evidence By Alan J. Auerbach and Kevin A. Hassett * The Jobs and Growth Tax Relief Act of 2003 (JGTRA03) reduced the tax rates on dividends, with the highest statutory tax rate of 35 percent falling to 15 percent. An interesting twist on the dividend tax cut was its temporary nature; the provision as passed was effective only through 2008, and (as recent Congressional deliberations have illustrated), the extension its supporters envisioned was by no means certain. This large dividend tax reduction, along with its sunset provision, offers an unusual natural research experiment on the effects of dividend taxation. The theory of dividend taxation suggests three possible scenarios for the effects of the dividend tax reduction. Under the “tax irrelevance” view, the marginal shareholder is a tax-free entity (or a taxable investor who ignores or can offset incremental taxes), and the dividend tax reduction has no effect on equity values or firm behavior. Under the “traditional” view the marginal source of equity finance is new share issuance, and the tax reduction feeds through to the firm’s user cost and stimulates extra capital formation. Share values rise in the short run but, after full adjustment, the higher capital level reduces the marginal revenue product of capital enough to offset the dividend tax reduction, leaving equity prices the same. Under the “new” view, the marginal source of finance is retained earnings and the dividend tax cut is capitalized into the share price of the firm but has no investment effect. Understanding the economic consequences of the dividend tax reduction requires knowledge of the empirical relevance of these competing views. Our previous paper (Auerbach and Hassett 2005) performed an event-study analysis of a large panel of firms to determine how firm attributes affected the valuation response over eight key event dates leading up to the 2003 legislation. Our results, taken together, rejected outright